Food risk in consumers' eye and their consumption responses: evidence from Hanoi survey - Ha TM; Shakur S; Pham Do KH (Emerald Publishing Limited, 2021)
Purpose This paper analyses Hanoi consumers' evaluation of food risk and response to the perceived risk. Design/methodology/approach The authors employed the mixed method approach that integrates segmentation analysis on the survey data and information from group discussions. Findings Based on consumers' risk rating of six food groups and level of food safety worry, the authors identified four distinct consumer segments: low, moderate, high and very-high-risk perception. The authors found the existence of widespread food safety concerns among Hanoi consumers. Living in an urban region was associated with a higher level of food risk perception. Moderate, high and very-high-risk perception segments exhibited a very low level of institutional trust and subjective control over hazards. Response to the perceived risk differed across segments. “Very high-risk perception” was associated with the most risk-averse behaviour, putting more effort into seeking food safety information and engaging more in supermarket purchase. Consumers with a low and moderate perceived food risk participate more in self-supply of food to reduce their food safety concern. Practical implications The paper provides empirical evidence on consumers' evaluation of food risk and their risk-reducing strategies to support the risk communication in Vietnam. Social implications Enhancing institutional trust and risk communication including hazard education can improve consumer confidence in food. Originality/value This is the first segmentation study on consumer food risk perception in Vietnam.
Keywords: Food safety; Risk perception; Risk reduction strategies; Vegetables